Toxicity of mercury (Hg) on survival and growth rate, hemato- and histopathological parameters ofOreochromis niloticus - Kukuh Nirmala; Yuni Puji Hastuti; Vika Yuniar (Jurnal Akuakultur Indonesia)
Heavy metals are serious pollutants of the aquatic environment because of their environmental persistence and ability to be accumulated by aquatic organisms. Oreochromis niloticus exposed to 0, 0.16, 0.5, and 1.0 ppm Hg for 30 days. The aim of this study was to determine the influence of mercury in water on survival rate, growth rates, hematological, and histological parameters of Oreochromis niloticus. This study was conducted from Mei to June 2009. The experimental design was arranged in completely randomized design with four treatments and three replications. Stock density was 8 fish/aquarium with mean initial body weight was 15.70±1.13 g. Growth and survival rates of test fish were decreased with increasing the Hg concentration. Red blood cell (RBC) count, haematocrit content, and haemoglobin content decreased when compared to the control. The number of white blood cells (WBC) increased in mercuric treated fish. The results are statistically significant at p<0.05 level.